1984
DOI: 10.1111/j.1471-4159.1984.tb00935.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Stimulated Release of Dopamine with In Vivo Voltammetry. I: Characterization of the Response Observed in the Caudate Nucleus of the Rat

Abstract: Microvoltammetric electrodes were employed in the brain of an anesthetized rat to monitor chemical substances in extracellular fluid following electrical stimulation of the medial forebrain bundle. An increase in concentration of an easily oxidized substance is observed in the caudate nucleus and in the nucleus accumbens. A large amount of evidence suggests that the substance that is observed following stimulation is dopamine. (1) The location of the stimulating electrode must be in known dopaminergic tracts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(87 citation statements)
references
References 27 publications
8
79
0
Order By: Relevance
“…However, microdialysis assay indicated no significant increase in dopamine concentration in the striatal ECF in the present study. One possible explanation for this discrepancy is that the change in dopamine concentration in ECF measured by microdialysis does not reflect the "true" dopamine release into the synaptic cleft as suggested previously using voltammetry (Kuhr et al, 1984;Kuhr and Wightman, 1986;May, 1988;Grace, 1993). This is unlikely however, because our previous study demonstrated that the same microdialysis assay could detect the enhancement of dopamine synthesis in the neurons (Tsukada et al, 1994a,b), the facilitation of dopamine release by methamphetamine (Tsukada et al, 1999a), and also the increase in the synaptic dopamine level induced by the inhibition of DAT by cocaine and GBR12909 (Tsukada et al, 1999a,b).…”
Section: Discussionmentioning
confidence: 79%
“…However, microdialysis assay indicated no significant increase in dopamine concentration in the striatal ECF in the present study. One possible explanation for this discrepancy is that the change in dopamine concentration in ECF measured by microdialysis does not reflect the "true" dopamine release into the synaptic cleft as suggested previously using voltammetry (Kuhr et al, 1984;Kuhr and Wightman, 1986;May, 1988;Grace, 1993). This is unlikely however, because our previous study demonstrated that the same microdialysis assay could detect the enhancement of dopamine synthesis in the neurons (Tsukada et al, 1994a,b), the facilitation of dopamine release by methamphetamine (Tsukada et al, 1999a), and also the increase in the synaptic dopamine level induced by the inhibition of DAT by cocaine and GBR12909 (Tsukada et al, 1999a,b).…”
Section: Discussionmentioning
confidence: 79%
“…Stimulated dopamine release The surgical procedure, stimulation parameters, and electrodes and apparatus have been described in detail in a previous publication (Kuhr et al, 1984). Male Sprague-Dawley rats were anesthetized with chloral hydrate and placed in a stereotaxic frame.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that stimulation of this neuronal tract causes a release of dopamine that can be monitored with a carbon fiber voltammetric electrode implanted at the caudate nucleus Ewing et al, 1983;Kuhr et al, 1984). Dopamine has been identified as the compound detected in the caudate nucleus by voltammetric, anatomical, physiological, pharmacological, and postmortem data.…”
mentioning
confidence: 99%
“…This may explain why some groups, using lower stimulation frequencies, reported that higher optimum frequencies were needed to reach maximum activation of dopamine neurones when applying shorter stimulation periods. These parameters ranged from 15 s at 100 Hz for dopamine release from the rat median eminence (Sarkar, Gottschall, Meites, Horn, Dow, Fink & Cuello, 1983) to 10 s at 60 Hz for dopamine release from the rat caudate nucleus (Kuhr, Ewing, Caudill & Wightman, 1984), 2 min at 30 Hz for dopamine release from the cat caudate (Voigtlander & Moore, 1971) for 20 min at 15 Hz for increased dopamine synthesis in the rat neostriatum (Murrin & Roth, 1975). Recently, significant levels of dopamine release from the isolated rat n.i.l.…”
Section: F-------------------------------------------mentioning
confidence: 99%